The rise of exosome-mediated mechanisms in MSC therapy - Weihua Liu; Sheng Chen; Yuan Wang; Wei Gong (Journal of Translational Medicine)
Abstract Background Graft-versus-host disease (GVHD) remains a critical complication following allogeneic hematopoietic cell transplantation. Mesenchymal stromal cells (MSCs) have demonstrated promising immunomodulatory effects in mitigating GVHD. Despite the growing body of research, a comprehensive bibliometric evaluation of MSCs in GVHD is still lacking. Objective To perform a bibliometric analysis of global research on MSC-based therapies for GVHD using Citespace and VOSViewer, with the aim of mapping publication trends, collaboration networks, and emerging research hotspots. Methods Publications from 2010 to 2023 were retrieved from the Web of Science using targeted search strategies. Data analysis was conducted using Citespace, VOSViewer, and the R package “bibliometrix” to construct co-authorship, co-citation, and keyword networks. Visualization maps were generated to illustrate publication trends, geographic distributions, and thematic evolution in MSC-GVHD research. Results A total of 875 relevant publications from 58 countries were identified. The analysis revealed a substantial increase in research output over the past decade, with a noTable focus on extracellular vesicle and exosome-mediated mechanisms in MSC therapy. Prominent collaboration networks were observed among leading countries, notably between the United States and China, and key authors and institutions were delineated. Emerging hotspots and trends in MSC-GVHD research were identified, underscoring areas of potential translational significance. Conclusion This bibliometric study provides a comprehensive overview of the evolving landscape of MSC research in GVHD. The findings highlight significant global trends and collaboration patterns that can inform both future basic research and clinical translation. These insights are critical for guiding further exploration and optimization of MSC-based therapeutic strategies in GVHD.